Double-balloon catheter and sequential oral misoprostol versus oral misoprostol alone for induction of labour at term: a retrospective cohort study. (September 2016) - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Heimrich, Jutta; Beckmann, Matthias W.; Faschingbauer, Florian; Sütterlin, Marc
Abstract: Objective: To evaluate the efficacy of induction of labour using a double-balloon catheter and, if necessary, sequential oral misoprostol without delay after removal of the catheter, in comparison with oral misoprostol alone. Study design: This retrospective cohort study included women undergoing induction of labour with oral misoprostol or double-balloon catheter with sequential oral misoprostol in singleton pregnancies at term. The catheter was placed in the evening and removed when there was no onset of labour within 12 h. Then oral misoprostol was started within 3 h. Primary outcome measure was the caesarean section rate. Results: There were 13, 082 deliveries during the study period with 3466 labour inductions out of which 1032 were eligible and analysed. The caesarean section rate was significantly lower in the double-balloon catheter group (26.1% vs. 17.3, p  = 0.021). Furthermore, in the combination group, the induction-to-delivery interval was shorter (median values 1144 vs. 1365 min, p  = 0.001) and there were more deliveries within 24 h (51.9 vs. 64.7%, p  = 0.003) and 48 h (87.4 vs. 95.8%, p  = 0.002). When stratifying for parity, there were less caesarean sections in the combination group (37.2% vs. 24.2%, p  = 0.015) in nulliparous women, too. In both, nulliparous and parous women, the induction-to-delivery interval was shorter (1742 vs. 1400 min, 0.005; 1020 vs. 912 min, p  = 0.018). Especially in parous women, the rates of delivery within 24 h (62.6% vs. 79.0%, p  = 0.007) and 48 h (88.6% vs. 99.0%, p  = 0.007) were higher in the combination group. Conclusion: Double-balloon catheter and sequential oral misoprostol without long delay in absent onset of labour after removal of the catheter resulted in less caesarean section and shorter induction-to-delivery interval in comparison with oral misoprostol alone.